GAMIFICATION AS A NEW DIGITAL ASSESSMENT TOOL (International Conference on Economics, Finance, Banking and Management, 2025)
The article examines gamification as a modern digital tool for assessing academic achievements. The advantages of this approach are analyzed: increasing learning motivation, developing self-assessment skills, and creating a personalized educational trajectory. The importance of immediate feedback and visualization of progress is emphasized as important factors for the success of gamified assessment. Special attention is paid to digital platforms and technological solutions that make it possible to effectively implement gamified assessment systems in the educational process.